Effect of COVID-19 Lockdown on Small Animal Trauma Patterns in Australia: A Multicentre Study - Hickey, Mara C.; Napier, Elizabeth; Ong, Hui Mei (Frontiers in Veterinary Science, 2022)
Objective – To determine whether patterns of trauma changed following the start of local lockdowns due to COVID-19. Design – Multi-institutional retrospective study assessing patients presenting within two years prior to local lockdown due to COVID-19 and one year following lockdown inclusive. Setting –Two university teaching hospitals and one private referral centre in Australia Animals – Dogs and cats with a presenting complaint of known or suspected trauma Interventions – Patient signalment, date of presentation, trauma type, treatment interventions and patient outcome (survival to discharge, cardiopulmonary arrest, or euthanasia) were recorded in a web-based data capture system (REDCap). Measurements and Main Results – 3189 patients (682 cats and 2507 dogs) were included in the study. Overall trauma prevalence was 2.9% with pre-lockdown prevalence of 2.8% and post-lockdown prevalence of 3.1% (p < 0.001). Cats had higher rates of blunt trauma while penetrating trauma was more prevalent in dogs (p < 0.001). Juvenile patients were also more likely to have blunt trauma when compared to adult patients (p < 0.001). Patient age and sex characteristics did not differ when comparing the 2 time periods. Compared to pre-lockdown, blunt and penetrating trauma patterns changed post-lockdown in dogs and cats (p < 0.001 for both). Interventions were performed more frequently (p = 0.039) in the post-lockdown with surgical procedures having a significant increase (p = 0.015). Survival rates increased post-lockdown for both species (p < 0.001) with financially driven euthanasia being less common than in pre-lockdown for dogs (p = 0.02). Conclusions – Trauma patterns changed for cats and dogs in the post-lockdown period. Compared to pre-lockdown, trauma prevalence was higher with a decrease in mortality rate. No increase in juvenile patients was identified post-lockdown. A decrease in financially driven euthanasia and an increase in interventions suggest no negative financial effect from COVID-19 lockdown on trauma patient care in Australia.